Infection patterns and molecular data reveal host and tissue specificity of Posthodiplostomum species in centrarchid hosts. Issue 11 (12th March 2018) - Boone, Evan C.; Laursen, Jeffrey R.; Colombo, Robert E.; Meiners, Scott J.; Romani, Michael F.; Keeney, Devon B.
Abstract: Posthodiplostomum minimum utilizes a three-host life cycle with multiple developmental stages. The metacercarial stage, commonly known as 'white grub', infects the visceral organs of many freshwater fishes and was historically considered a host generalist due to its limited morphological variation among a wide range of hosts. In this study, infection data and molecular techniques were used to evaluate the host and tissue specificity of Posthodiplostomum metacercariae in centrarchid fishes. Eleven centrarchid species from three genera were collected from the Illinois portion of the Ohio River drainage and necropsied. Posthodiplostomum infection levels differed significantly by host age, host genera and infection locality. Three Posthodiplostomum spp. were identified by DNA sequencing, two of which were relatively common within centrarchid hosts. Both common species were host specialists at the genus level, with one species restricted to Micropterus hosts and the other preferentially infecting Lepomis . Host specificity is likely dictated by physiological compatibility and deviations from Lepomis host specificity may be related to host hybridization. Posthodiplostomum species also differed in their utilization of host tissues. Neither common species displayed strong genetic structure over the scale of this study, likely due to their utilization of bird definitive hosts.